2023
DOI: 10.3390/ijerph20032434
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use among Polish Students: Prevalence, Relationship to Sociodemographic Data and Internet Usage Patterns

Abstract: Problematic Internet Use (PIU) is a broad term that covers problems with Internet use that result in psychological, social, academic or professional difficulties. The aim of our study was to identify individuals particularly vulnerable to developing PIU among Polish students, taking into account sociodemographic characteristics and Internet use patterns. A total of 1008 students of Polish universities took part in the survey. The research tool was The Problematic Internet Use Test—the Polish version of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…This is a bit surprising, considering that most other studies have reported a much lower prevalence of PIU. For instance, the reported prevalence of PIU in young people only ranged from 10.2% to 45.1% in several studies in recent years (including those conducted during the COVID-19 pandemic) [2][3][4][5][6]. We notice that [1] used a cutoff of the IAT score > =50 to define PIU, which is in line with many earlier studies using the same tool [7,8].…”
supporting
confidence: 87%
“…This is a bit surprising, considering that most other studies have reported a much lower prevalence of PIU. For instance, the reported prevalence of PIU in young people only ranged from 10.2% to 45.1% in several studies in recent years (including those conducted during the COVID-19 pandemic) [2][3][4][5][6]. We notice that [1] used a cutoff of the IAT score > =50 to define PIU, which is in line with many earlier studies using the same tool [7,8].…”
supporting
confidence: 87%
“…The role of these social factors are rarely studied among problematic users, only a few studies have dealt with the topic before [ 34 ]. The lack of a person of trust to talk to as well as being online instead of meeting with close friends may increase the possibility of PUI [ 34 , 39 , 42 ]. Being physically active (doing sports etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Age, education, employment status, and rural/urban residence may not have been strong predictors of Internet addiction in this particular sample, based on the lack of significant associations between other sociodemographic and lifestyle characteristics and strong Internet addiction in our study. It is crucial to keep in mind that we used a specific sample with certain features and, as a result, the conclusions may not apply to other groups (35,36). To fully comprehend the complicated relationship between Internet addiction and different sociodemographic and lifestyle aspects, more research is required.…”
Section: Discussionmentioning
confidence: 99%